ANALISIS DAN IMPLEMENTASI SISTEM APLIKASI INVENTORY ITEMS BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Auliya Rahman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Application Inventory is an application to determine a list of facilities that exist in all parts, including the buildings and stuff. Inventory aims to provide identification for all existing facilities in a private company or government agency. Invenatris made should contain information that is clear and easy to understand, so it can help smooth work. Thus the inventory of maintenance work will be easier. Making the application of this inventory can help the performance of companies in managing inventory data items with a computerized system. The method used is comprised of several stages of analysis, design, implementation, maintenance. Implementation of the system design using the programming language PHP and My SQL as the database. Web-based inventory application using CodeIgniter framework to assist companies in managing inventory data such as data entry of goods, damaged, ownership of goods, procurement of goods, damaged goods, refinement of goods and movement of goods. Keywords: Application, inventory, php, mysql, CodeIgniter framework